2021
DOI: 10.1029/2020wr028670
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Time‐Frequency Signal Processing Methods for Identifying Non‐Perennial Streamflow Events From Streambed Surface Temperature Time Series

Abstract: Nonperennial stream networks constitute over half of total stream lengths worldwide (Datry et al., 2014). However, knowledge of the spatial and temporal variability of non-perennial flows is often limited (Costigan et al., 2016) and stream gauging networks are typically biased toward perennial streams (De Girolamo et al., 2015;Eng et al., 2016). Even where gauges on nonperennial streams exist, often insufficient data are available to identify spatial variations in flows within a catchment. Since the duration a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 85 publications
0
6
0
Order By: Relevance
“…(2001) and Partington et al. (2021), who found a damping effect in temperatures in the soil beneath the riverbed because of rainfall or streamflow events in nonperennial streams.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…(2001) and Partington et al. (2021), who found a damping effect in temperatures in the soil beneath the riverbed because of rainfall or streamflow events in nonperennial streams.…”
Section: Discussionmentioning
confidence: 97%
“…(2001) and Partington et al. (2021). These authors found interruptions in the daily soil temperature cycle during water flow events in nonperennial streams comparable to saturated infiltration into an agricultural soil.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Recent improvements in sensor technology gave the opportunity to use high‐resolution photography, remote sensing (Dralle et al., 2023; Shawky et al., 2019; Spence & Mengistu, 2016), and other innovative devices to support the monitoring of the stream length variations. Notable examples include temperature sensors (Arismendi et al., 2017; Blasch et al., 2004; Constantz et al., 2001; Keery et al., 2007; Partington et al., 2021), stage camera systems (Herzog et al., 2022; Kaplan et al., 2019; Noto et al., 2022; Perks et al., 2016; Tauro et al., 2014; Tauro, Olivieri, et al., 2016; Tauro, Petroselli, et al., 2016), and electrical resistance sensors (Chapin et al., 2014; Floriancic et al., 2018; Goulsbra et al., 2014; Jensen et al., 2019; Kaplan et al., 2019; Paillex et al., 2020; Zanetti et al., 2022). All of them proved to be useful for collecting data at high temporal resolution and have the benefit of being cost‐effective and automatic, allowing scientists to observe the sequences of activation/deactivation of the different nodes of the network (Durighetto et al., 2023) and any discontinuity in the wet stream length at the event scale, rather than at the monthly or seasonal scale.…”
Section: Introductionmentioning
confidence: 99%
“…At present, the identification methods based on the signal characteristics of electromagnetic signals mainly use manual methods to extract signal characteristics and realize discrimination [5]. Common electromagnetic signal feature extraction methods include time domain analysis [6], frequency domain analysis, instantaneous autocorrelation, spectral correlation and time-frequency domain analysis. These methods generally transform the sampled signal and extract its features [7], and realize signal recognition through the feature vectors with high separability.…”
Section: Introductionmentioning
confidence: 99%